THE INFLUENCE OF WORK DISCIPLINE AND WORK SPIRIT ON MEDICAL EMPLOYEE PERFORMANCE IN THE WOMEN'S EMPOWERMENT OFFICE OF POPULATION CONTROL AND FAMILY PLANNING IN THE CITY OF TEXAS - Arnaud Costinot; Mohsen Bahmani-Oskooee (PT. Radja Intercontinental Publishing, 2023)
The results of this study show. (1) It can be seen that the adjusted R square value is 0.774 or 77.4%. This shows that the Work Discipline Variable (X1) and Work Morale Variable (X2) can explain the Employee Performance Variable (Y) of 77.4% , the remaining 22.6% (100% - 77.4%) is explained by other variables outside this research model. (2) The results of the (Partial) t test show that tcount (6.481) > ttable (1.990), likewise with a significance value of 0.00 > 0.05, it can be concluded that the first hypothesis is rejected, meaning that the Work Discipline Variable (X1) has an effect not significant to Employee Performance Variable (Y). (3) The results of the t test (Partial) can be seen that the tcount (7.650) > ttable (1.990), and the significance value is 0.00 <0, 05, it can be concluded that the second hypothesis is accepted, meaning that the Morale Variable (X2) has a significant effect on the Employee Performance Variable (Y). (4) The results of the simultaneous test (F) can be seen that the Ftable value is 3.22. From this description it can be seen that Fcount (69.631) > Ftable (3.24), and a significance value of 0.00 <0.05, it can be concluded the third hypothesis is accepted, meaning that the Work Discipline Variable (X1), the Work Morale Variable (X2) have a significant simultaneous effect on the Employee Performance Variable (Y).